Effective inclusion of talented students in the current school in the framework of the Capacity Development Program - Esther Cascarosa Salillas; Carlos Lorda Pérez; Begoña Martínez Peña (Universidad de La Rioja, 2019)
The main purpose of this work was to investigate how the introduction of active and participatory methodologies with talented students, favors on the one hand the talents to come and will be rewarded and, on the other hand, facilitates positive social interactions to the work as a team. An inclusive school must guarantee an education adapted to every student based on their own needs and interests. However, the design of the current educational system greatly hinders faculty bet by methodologies that foster the development of skills in the students in general and in particular the students with skills. Through the implementation of the Capacity Development Program, talented students have developed projects based on their own interests. Data based on structured questionnaires, observation sheets and interviews have been collected. Results shown in the present work, prove that the capacity development program is a suitable context to work in learning environments that commit to the students (and families) in the construction of their own knowledge. This program is a useful framework for the development of the students´ learning as they would outside the school, using ICT and collaborative work, as main tools.